Route to access imidazol[1,5-a]indole-1,3-diones and pyrrolo[1,2-c]imidazole-1,3-diones - Rao, Ramana Sreenivasa; Shajan, Fere Joseph; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2019)
A novel and practical route to synthesize imidazol[1,5-a]indoles and pyrrolo[1,2-c]imidazoles via N-H functionalization has been developed. Indole-2-carboxylic acid or pyrrole-2-carboxylic acid with diverse aniline groups and carbonyldiimidazole (CDI), in the presence of a base under microwave conditions, resulted in imidazol[1,5-a]indoles and pyrrolo[1,2-c]imidazoles, respectively. The present method is free of work-up and no need for column chromatography. Both title scaffolds can serve as useful heterocyclic scaffolds in medicinal chemistry as such, or they can be used as building blocks to construct different classes of useful compounds.